Rapid mass spectrometric identification of human genomic polymorphisms using multiplexed photocleavable mass-tagged probes and solid phase capture. - Hammond, N; Koumi, P; Langley, G; Lowe, A; Brown, T (2007)
A mass spectrometric approach for rapid and simultaneous detection of several single nucleotide polymorphisms (SNPs) is reported. Oligonucleotide single base extension (SBE) primers, labelled at the 5'-end with photocleavable, quaternised and brominated peptidic mass tags, are extended by a mixture of the four dideoxynucleotides of which one is biotinylated. The 3'-biotinylated extension products are captured by streptavidin-coated solid phase magnetic beads, whilst non-biotinylated extension products and unreacted primers are washed away. Quaternised and brominated mass tags, cleaved from captured extension products during analysis by matrix-assisted laser desorption/ionisation-time-of-flight (MALDI-TOF) MS, are detected at pmol levels. This method is applied to the analysis of mitochondrial DNA polymorphisms for the purpose of human identification.